DINAMIKA DAN IMPLEMENTASI HUKUM ORGANISASI PERUSAHAAN DALAM SISTEM HUKUM INDONESIA: Dynamics and Implementation of Corporate Organizational Law within the Indonesian Legal System - Muhibbuthabary, Muhibbuthabary (Asy-Syari'ah, 2016)
The legal system in Indonesia explained that the act of commerce is the act of purchasing goods for resale. While the organization is a coordination unit comprising at least two people, has a function to achieve a certain goal or set of tools. the company is a unit of business organizations that produce goods and services to meet the needs of the community with the aim of the company is a unit of business organizations that produce goods and services to meet the needs of the community with the aim to obtain profit. The company is a business organization that has carried out business activities and continuous, uninterrupted and overt move out with the aim toÂ get benefit. In the Code of Commercial Law mentioned that perbu-atan commerce on the organization of the company is the act of purchase does not include sales deeds, because sales is part of the aim of business. In practice, the legal system of Indonesia has set about permit the establishment and governance of enterprise organizations are legal entities such as limited liability, Firma, cooperatives, foundations, enterprises, and etc. This has been stipulated in the legislation, namely Law Number 3 of 1992 about the Registration Company and Law Number 8 of 1997 concerning Company Documents.